Copyright Protection for AI Usage of Song in the Era of Digital Disruption - Tamarischa Pradhipta; Ery Agus Priyono (Dinasti Research, 2025)
Artificial intelligence (AI) is a technology designed to mimic human intellectual abilities to improve efficiency and effectiveness in various fields. As technology advances, AI has been widely adopted in everyday life, from the creative industry, health, to education. One of the latest examples is the Meta AI feature on WhatsApp, which makes it easier to interact and process data. Although AI provides many benefits, its emergence also poses challenges, especially related to copyright protection, such as in the ChatGPT chatbot and AI voice cloning technology in the music industry. AI allows for high-accuracy voice replication, which has the potential to cause copyright infringement in music creation. Therefore, clear legal regulations and the application of ethics in the use of AI are needed so that its development can have a positive impact on society.